Hubungan Konsep Diri dengan Kepercayaan Diri Anak Broken Home di Madrasah Aliyah Muhammadiyah Pasaman Barat - Annisa, Sofia; Santosa, Budi (Lembaga Yasin AlSys, 2023)
Self-concept is related to self-confidence, because self-concept is one of the things that influences a child's self-confidence, self-confidence includes perceptions, feelings, beliefs, and self-assessments, and someone who has a low self-concept can cause a person's low self-confidence. This study aims to, 1) determine the relationship between self-concept and the self-confidence of broken home children, 2) find out how much the relationship between self-concept and the self-confidence of broken home children. This type of quantitative research is correlational. The research population of West Pasaman Muhammadiyah Aliyah Madrasah Aliyah students who experienced broken home families was 20 students. The sampling technique is total sampling. Data collection techniques using self-concept and self-confidence instruments. Data analysis techniques used non-parametric analysis techniques and the correlation used the Spearman rho method with the help of SPSS version 26. Based on the results of the hypothesis testing, the results obtained were rcount 0.499 > rtable 0.443 that Ho was rejected and Ha was accepted. This means that there is a significant correlation between self-concept and the self-confidence of broken home children at Madrasah Aliyah Muhammadiyah Pasaman Barat. Interpreting the non-parameric correlation can be concluded that 0.499 lies (0.40-0.599), namely between variable X (self-concept) and variable Y (self-confidence). There is a correlation, which means it is moderately correlated. Based on the results of the study, it was concluded that the better (positive) the student's self-concept, the higher the student's self-confidence. and vice versa, the worse (negative) the student's self-concept, the lower the student's self-confidence.